Oil Palm Plantation Expansion: Changes in Agrarian Structure and Food Security of Rural Households in Kanamit Village - Suprojo, Baskara; Affandi, Muhamad Irfan (Jurnal Geospasial Indonesia, 2025)
Oil palm is the leading cash crop with the and most extensive cultivation in the tropics, especially in Indonesia. The area of oil palm plantations in Pulang Pisau Regency covers 17,031.63 ha, with 2,762.32 ha allocated to smallholders and the remainder to private estates. The expansion of oil palm plantations is of interest to conduct a study in Kanamit Village, which is adversely affected by the agrarian structure and its impact on food security. This research employs a mixed-methods approach, combining quantitative methods to assess food security and qualitative methods to describe changes in agrarian structure. The results show that there have been changes in land ownership, control, use, and utilization due to the entry of private estates. The food security of the community is mainly in the vulnerable category, with the proportion of food expenditure >60%, while the level of energy consumption (TKE) is <80%. The integration of agrarian structure and food security decision-makingin this research can serve as a decision-making tool for stakeholders to take action in protecting the community's needs in Kanamit Village or other areas.